Development of modeling methodology for hydrogeological heterogeneity of the deep fractured granite in Japan. (August 2021) - Onoe, Hironori; Ishibashi, Masayuki; Ozaki, Yusuke; Iwatsuki, Teruki
Abstract: Constructing and operating a large underground facility for the geological disposal of high-level radioactive waste for decades will cause changes in the geological environment around the underground facility. Since the permeability and heterogeneity of fractured granite in Japan are higher than those in Europe, the disturbance to the groundwater environment due to tunnel excavation is expected to be large and complex. Therefore, modeling of fracture characteristics is important to accurately predict changes in the geological environment due to the construction and after the closure of the underground facility. However, the modeling approach focused on the fractured granite deeper than several hundred meters has not been completely established in Japan. Therefore, in this study, we investigated the methodology of modeling for fractured granite around the drift at a depth of 500 m in the Mizunami Underground Laboratory, Japan as a case study. As a result, we developed the fracture modeling method to estimate not only geological parameters of fractures but also hydraulic parameters based on the reproducibility of trace length distribution of fractures. By applying this modeling method, it was possible to construct a Discrete Fracture Network (DFN) model that can accurately reproduce the statistical characteristics of fractures. Besides, the application of the conditioning method to correct the fracture location and transmissivity to match the observation data to a specific site was demonstrated to enable the evaluation of local fracture characteristics. Furthermore, the relationship between the in-situ investigation and the data required for the modeling of hydrogeological heterogeneity of the fractured granite was clearly described, and the strategy of in-situ investigation, modeling, and disposal panel design for fractured granite using the DFN modeling during the underground facility construction phase as a useful knowledge of the geological disposal project in Japan was proposed.